1998
DOI: 10.1161/01.str.29.3.625
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Superficial Temporal Artery–Middle Cerebral Artery Anastomosis in Adult Moyamoya Disease

Abstract: Background and Purpose-The efficacy of superficial temporal artery-middle cerebral artery (STA-MCA) anastomosis in adult moyamoya disease was evaluated by clinicopathophysiological studies. Methods-Fifteen patients with cerebral ischemic attacks (ischemia group) and 15 patients with intracranial hemorrhages (hemorrhage group) were investigated. Clinicoangiographic features and regional cerebral blood flow (rCBF) of the MCA territory were preoperatively and postoperatively investigated, and cortical arterial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(72 citation statements)
references
References 28 publications
1
69
0
2
Order By: Relevance
“…Although the precise mechanism of hemorrhage in moyamoya disease remains unknown and no definite preventive treatment has been devised 6) , researchers continue to find better ways of preventing hemorrhage [5][6][7]10,13,15) . Many reports have addressed treatment options for reducing the rates of re-bleeding in hemorrhagic moyamoya disease 4,10,13,15,16) ; however, reductions in re-bleeding incidents in hemorrhagic moyamoya patients after surgical treatment are difficult to assess due to a lack of long-term postoperative follow-up data 14,15) . Nevertheless, bypass surgery is a powerful tool in this area because it likely aids in the prevention of re-bleeding, which increases the blood flow in revascularized collateral vessels and reduces the number of moyamoya vessels 10,13) .…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise mechanism of hemorrhage in moyamoya disease remains unknown and no definite preventive treatment has been devised 6) , researchers continue to find better ways of preventing hemorrhage [5][6][7]10,13,15) . Many reports have addressed treatment options for reducing the rates of re-bleeding in hemorrhagic moyamoya disease 4,10,13,15,16) ; however, reductions in re-bleeding incidents in hemorrhagic moyamoya patients after surgical treatment are difficult to assess due to a lack of long-term postoperative follow-up data 14,15) . Nevertheless, bypass surgery is a powerful tool in this area because it likely aids in the prevention of re-bleeding, which increases the blood flow in revascularized collateral vessels and reduces the number of moyamoya vessels 10,13) .…”
Section: Discussionmentioning
confidence: 99%
“…Although some reports have demonstrated the effects of direct revascularization surgery to prevent recurrent bleeding [13], or at least subsequent ischemia [20], the long-term efficacy of revascularization surgery following hemorrhage in adult patients remains controversial [2,6,22,27]. On the other hand, moyamoya disease in childhood manifests cerebral infarction more frequently than in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric patients mainly present with cerebral ischemia and they very rarely bleed [2,4,14,15]. Although the benefits of surgical revascularization for ischemic moyamoya disease have been well recognized, the indications for such treatment in hemorrhagic type to prevent rebleeding have not yet been established [2,6,13,20,22,27]. We herein report three children aged < 10 years presenting with intracerebral hemorrhage associated with moyamoya disease, two of which were accompanied with early ischemic complications followed by revascularization surgery.…”
Section: Introductionmentioning
confidence: 93%
“…A bypass surgery for this type of moyamoya disease could prevent recurrent hemorrhage by reducing the hemodynamic stress. Several reports evaluating the efficacy of direct bypass surgery for this disease type suggested that surgery could lead to a positive clinical outcome 3,5,10,18,50,60,61) ; however, surgical treatment for hemorrhagic moyamoya disease is still not widely accepted. To establish treatment guidelines for hemorrhagic moyamoya disease, the Japan Adult Moyamoya trial was initiated as a multicenter prospective randomized trial in 2001.…”
Section: Stage 6: Surgical Treatment For the Hemorrhagic Type Of Moyamentioning
confidence: 99%